Association between neutrophil/lymphocyte ratio and coronary collateral circulation. Issue 1 (2012) - Çil, Habib; İslamoğlu, Yahya and Yavuz, Celal and Atılgan, Zuhal Arıtürk and Çalışkan, Ahmet and Demirtaş, Sinan and Oylumlu, Mustafa
No abstract available